Tea with the dames [videorecording (DVD)] - Atkins, Eileen, 1934-; Dench, Judi, 1934-; Plowright, Joan; Smith, Maggie, 1934- (IFC Films, 2019)
Dame Maggie Smith, Dame Judi Dench, Dame Eileen Atkins, and Dame Joan Plowright are among the most celebrated actresses of the time, with scores of iconic performances, decades of wisdom, and innumerable awards between them. They are also longtime friends who invite viewers to join them for a weekend in the country as they catch up with one another, reminisce, and share their candid, delightfully irreverent thoughts on everything from art to aging to love to a life lived in the spotlight.